FDTD simulation of radiation characteristics of half-volume HEM and TE-mode dielectric resonator antennas. - O'Keefe, S.G.
Cylindrical and rectangular dielectric resonator antennas (DRAs) using HEM11δ, TE11δ, and TE01δ mode were examined to see the radiation pattern, impedance, field distribution and resonant frequency that were achieved when the DRAs were bisected through an image plane by a conducting sheet. The resultant half DRAs are smaller in volume and have a more directional radiation pattern. The elevation angle of maximum radiation was lowered in some cases. Finite-difference time-domain simulation techniques were used
Keywords: FDTD methods; HEM-mode dielectric resonator antennas; TE-mode dielectric resonator antennas; Conducting sheet; Cylindrical dielectric resonator antennas; Directional radiation pattern; Elevation angle; Field distribution; Half-volume dielectric resonator antennas; Impedance; Radiation characteristics; Rectangular dielectric resonator antennas; Resonant frequency